Rancang Bangun Sistem Monitoring Pelanggaran Siswa Berbasis Web Dan Android Studi Kasus Smp Negeri 1 Kasokandel - Dadan Zaliluddin; Yayat Sutaryat (PROCEEDING STIMA)
Implementation of the order in SMP Negeri 1 Kasokandel during this time can be said to be less going well. The reason was because there are many students of SMP Negeri 1 Kasokandel who can not obey and implement school rules well. There are still many students who violate the discipline that has been made by the school. Like for example, came too late, it can be seen every morning there are still some students who arrive late to school. Every Monday there are usually several students who were in the right rear builder ceremony for not wearing a hat or tie when the ceremony and some other forms of abuse. To meet the needs and demands of the above, the writer tries to make the application system monitoring violations of the student-based web and android that can be easily in the user (user friendly) by users of smartphones and can be updated at any time, the system is made by using a programming language-based web and android , while the web-based server for client-based android.Keywords: Design, Monitoring System Violation of Students, Web, Android